Inducing enhanced neutralizing antibodies against broad SARS-CoV-2 variants through glycan-shielding multiple non-neutralizing epitopes of RBD - Zhang, Qingyun; Yang, Yi; Lan, Jun; Wang, Ziyi; Gao, Yan; Li, Xiao; Mao, Weidong; Xie, Jing; Mi, Li-Zhi; Zhang, Xiangyang; Wang, Xinquan; Mu, Xin; et al. (Frontiers in Immunology, 2023)
Introduction Since the outbreak of SARS-CoV-2, vaccines have demonstrated their effectiveness in resisting virus infection, reducing severity, and lowering the mortality rate in infected individuals. However, due to the rapid and ongoing mutations of SARS-CoV-2, the protective ability of many available vaccines has been challenged. Therefore, there is an urgent need for vaccines capable of eliciting potent broadly neutralizing antibodies against various SARS-CoV-2 variants. Methods In this study, we developed a novel subunit vaccine candidate for SARS-CoV-2 by introducing a series of shielding glycans to the Fc-fused receptor-binding domain (RBD) of the prototypic spike protein. This approach aims to mask non-neutralizing epitopes and focus the immune response on crucial neutralizing epitopes. Results All modified sites were confirmed to be highly glycosylated through mass spectrometry analysis. The binding affinity of the glycan-shielded RBD (gsRBD) to the human ACE2 receptor was comparable to that of the wildtype RBD (wtRBD). Immunizing mice with gsRBD when combined with either Freund’s adjuvant or aluminum adjuvant demonstrated that the introduction of the glycan shield did not compromise the antibody-inducing ability of RBD. Importantly, the gsRBD significantly enhanced the generation of neutralizing antibodies against SARS-CoV-2 pseudoviruses compared to the wtRBD. Notably, it exhibited remarkable protective activity against Beta (B.1.351), Delta (B.1.617.2), and Omicron (B.1.1.529), approximately 3-fold, 7- fold, and 17-fold higher than wtRBD, respectively. Discussion Our data proved this multiple-epitope masking strategy as an effective approach for highly active vaccine production.